Structural Breaks and the Finance-Growth Hypothesis in ECOWAS: Further Empirical Evidence (2014)
This study makes a cross sectional case in investigating the validity, or otherwise, of the finance driven growth hypothesis in the ECOWAS countries using annual data from 1970 to 2008 for seven countries namely: Burkina Faso, Cote d’Ivoire, The Gambia, Ghana, Nigeria, Senegal and Togo. In contrast to earlier studies on developing countries, this study specifically tests for the possibility of structural breaks/regime shifts in the finance-growth long run relationship by employing the Gregory and Hansen (1996) residual based test which accounts for endogenous structural break. While the Gregory-Hansen structural break cointegration result confirms the existence of cointegration relationships among the selected countries despite the breakpoints, the Granger-causality test result indicates a general pattern of causality running from financial development to economic growth in most of the countries. Also, the striking feature of the result of our estimated growth model generally lends credent to the importance of financial development in explaining growth dynamics among the selected countries, thus reinforcing the finance-driven growth hypothesis.